Feasibility of Reprocessing Natural Fiber Filled Poly(lactic acid) Composites: An In-Depth Investigation - Sujal Bhattacharjee; Dilpreet S. Bajwa (Advances in Materials Science and Engineering)
Poly(lactic acid) (PLA) based composites are biodegradable; their disposal after single use may be needless and uneconomical. Prodigal disposal of these composites could also create an environmental concern and additional demand for biobased feedstock. Under these circumstances, recycling could be an effective solution, since it will widen the composite service life and prevent the excessive use of natural resources. This research investigates an in-depth impact of recycling on the mechanical and thermomechanical properties of oak wood flour based PLA composites. Two composite formulations (30 and 50 wt% filler), each with 3 wt% coupling agent (PLA-g-MA), were produced and reprocessed six times by extrusion followed by injection molding. Measurements of fiber length and molecular weight of polymer were, respectively, carried out by gel permeation chromatography (GPC). Scanning electron microscopy (SEM), differential scanning calorimetry (DSC), thermogravimetric analysis (TGA), and Fourier transform infrared spectroscopy (FTIR) tools were used to study morphological and molecular alterations. With consecutive recycling, PLA composites showed a gradual decrease in strength and stiffness properties and an increase in strain properties. The 50% and 30% filler concentration of fibers in the composite showed an abrupt decrease in strength properties after six and two reprocessing cycles, respectively.